The effect of the educational intervention on health literacy level in the girl students - Mitra Kahtari; Rabiollah Farmanbar; Parisa Kasmaei; Saeed Omidi (Mashhad University of Medical Sciences, 2017)
Background and objective: Health literacy represents the whole range of skills and resources that is related to individuals' ability to process information around health and wellness. The present study aimed to determine the effects of educational intervention on health literacy among female students in the second year of study at high school in the academic year of 95-96 at Siahkal city. Methods:It is a randomized, controlled trial. The population consists of 132 students (71 students in the intervention group, 61 students in the control group) who were selected between girl students in the second year of study at high school in Siahkal city via convenience sampling method and were divided randomly into one intervention group and one control group. To collect data, health literacy of student's questionnaire (HELMA) was used in two stages (pre-test and post-test). The intervention group was received four health literacy training sessions. Paired t-test, independent t-test and Mann-Whitney test were used to analyze the data using spss21 software. Results: The results indicated that there is a significant difference between the mean of domains of the two groups including reading skills, evaluating and computing domains. However, there is no significant difference between two groups in comparison of some skills such as accessing, understanding, communicating, self-efficacy, use and also the general domain study. Conclusion: The results showed that the use of educational intervention is effective on empowerment and improving the health literacy of girl students. It is evident in the area of understanding, calculating and evaluating the effects of intervention. Paper Type:Research Article.